Research on brand stickiness of gamification marketing under the perspective of immersion theory: Network social capital as mediating variable and fear of missing out as moderating variable effect - Han, YiJing; Chen, Sze-Ting (Edelweiss Applied Science and Technology, 2025)
The advent of the experience economy in the 21st century has driven the development of the immersive industry. Now, how companies can retain customers and foster high brand stickiness is an issue that organizations should consider. Therefore, this study establishes gamified marketing as the independent variable, brand stickiness as the dependent variable, network social capital as the mediating variable, and fear of missing out (FOMO) as the moderating variable, based on immersive theory. Using a regional stratified sampling method, a total of 986 valid questionnaires were collected and analyzed through structural equation modeling. The results indicate that gamified marketing has a positive impact on brand loyalty. Additionally, network social capital mediates the relationship between gamified marketing and brand loyalty, while FOMO positively moderates this relationship. This study provides valuable guidance for businesses seeking to enhance user brand loyalty through gamified marketing, thereby increasing the likelihood of successful marketing implementation. It also strengthens the connection between consumers and businesses, helping to achieve marketing objectives and offering theoretical support for acquiring loyal customers.